2021
DOI: 10.1093/nar/gkab108
|View full text |Cite
|
Sign up to set email alerts
|

Conserved dual-mode gene regulation programs in higher eukaryotes

Abstract: Recent genomic data analyses have revealed important underlying logics in eukaryotic gene regulation, such as CpG islands (CGIs)-dependent dual-mode gene regulation. In mammals, genes lacking CGIs at their promoters are generally regulated by interconversion between euchromatin and heterochromatin, while genes associated with CGIs constitutively remain as euchromatin. Whether a similar mode of gene regulation exists in non-mammalian species has been unknown. Here, through comparative epigenomic analyses, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 66 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…The data described above indicate that not all CGI − genes are simultaneously up-regulated during aging: Some are more commonly misexpressed than others in cells that have disrupted nuclear/chromatin architecture. To investigate what determines this misexpression of some CGI − genes but not others, we tested whether it is affected by chromosomal gene organization, which provides information on the spatial positioning of the genes in the nucleus and their epigenetic regulation ( 8 10 , 16 , 17 ). We collected Hi-C chromatin conformation data generated from 28 healthy, young adult mouse tissues and cells ( n = 191; table S5A) and performed principal components analysis (PCA) to classify genomic regions in each sample as heterochromatin or euchromatin [represented by low or high PC1 values, respectively ( 21 )].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data described above indicate that not all CGI − genes are simultaneously up-regulated during aging: Some are more commonly misexpressed than others in cells that have disrupted nuclear/chromatin architecture. To investigate what determines this misexpression of some CGI − genes but not others, we tested whether it is affected by chromosomal gene organization, which provides information on the spatial positioning of the genes in the nucleus and their epigenetic regulation ( 8 10 , 16 , 17 ). We collected Hi-C chromatin conformation data generated from 28 healthy, young adult mouse tissues and cells ( n = 191; table S5A) and performed principal components analysis (PCA) to classify genomic regions in each sample as heterochromatin or euchromatin [represented by low or high PC1 values, respectively ( 21 )].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that CGI − genes in heterochromatic domains are rarely activated during aging suggests that loss of heterochromatin is not sufficient to activate all associated genes simultaneously but rather requires additional layers of regulation. As our prior studies demonstrated that CGI − genes are generally regulated by local binding of transcription factors (TFs) ( 8 10 ), we further performed TF-binding motif analysis. Notably, known TF-binding motifs were significantly more prevalent in the promoters of CGI − genes in euchromatic domains when compared to those in cHet domains ( P < 2.2 × 10 −16 for both), and this was even more evident in recurrently up-regulated CGI − genes (fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations